Lung Epithelial Cell Line Immune Responses to Pneumocystis - Theodore J. Kottom; Eva M. Carmona; Andrew H. Limper (Journal of Fungi, 2023)
Pneumocystis sp. are fungal pathogens and members of the Ascomycota phylum. Immunocompetent individuals can readily eliminate the fungus, whereas immunocompromised individuals can develop Pneumocystis jirovecii pneumonia (PJP). Currently, over 500,000 cases occur worldwide, and the organism is listed on the recently released WHO fungal priority pathogens list. Overall, the number of PJP cases over the last few decades in developed countries with the use of highly effective antiretroviral therapy has decreased, but the cases of non-HIV individuals using immunosuppressive therapies have significantly increased. Even with relatively effective current anti-Pneumocystis therapies, the mortality rate remains 30–60% in non-HIV patients and 10–20% during initial episodes of PJP in HIV/AIDS patients. Although the role of alveolar macrophages is well studied and established, there is also well-established and emerging evidence regarding the role of epithelial cells in the immune response to fungi. This mini review provides a brief overview summarizing the innate immune response of the lung epithelium and various continuously cultured mammalian cell lines to Pneumocystis.